Fatigue shear strength of slender web plate girders - Osman, Mohd. Hanim; Md. Tahir, Mahmood; Saad, Sarifuddin (Faculty of Civil Engineering, UTM, 2000)
A study on the fatigue strength of slender web plates subjected to repeated shear loading is described herein. A series of tests on 20 girders with slender web was carried out. The girders were subjected to cyclic loading of a certain range up to the formation of fatigue cracking. Stresses along the welded connection between the webs and flanges were measured during the tests. The correlation between the stresses and number of cycles of loading at failure was analysed and a new fatigue resistant curve was developed and incorporated into the standard design curve of fatigue resistant given in BS 5400:Part 10 and EC 3:Chapter 9. The resistant to fatigue failure for the welded web under shear loading was found to be high compared to other standard detail categories.